A compression algorithm for DNA sequences. - Xin Chen (IEEE Engineering in medicine and biology magazine)
We present a DNA compression algorithm, GenCompress, based on approximate matching that gives the best compression results on standard benchmark DNA sequences. We present the design rationale of GenCompress based on approximate matching, discuss details of the algorithm, provide experimental results, and compare the results with the two most effective compression algorithms for DNA sequences (Biocompress-2 and Cfact).